Soil velocity profile on soft soil using seismic refraction - Mad Said, Mohd Jazlan (2014)
Soil velocity profile often used as subsurface characterization by using geophysical techniques. Seismic refraction is one of geophysical technique to determine primary wave (p-wave) velocity of the soil profile. In this paper, seismic refraction technique has been performed on two different types of soft soil (peat soil and Soft clay) for comparison of its p-wave velocity soil profile. From p-wave velocity soil profile comparison, its show the peat soil has soil velocity range from 211 m/s – 534 m/s at depth of 0 – 4 m while the soft clay show soil velocity range from 248 m/s – 1842 m/s at depth of 0 – 5.5 m. The profiles of peat soils and Soft clay have been verified using peat samplers and existing borehole data. Both of velocity soil profiles, indicated that peat soil have lower velocity compare with soft clay due to its unique and soft soil characteristics. The difference of p-wave velocity soil profile between peat soil and soft clay are clearly showed both soils have different soil p-wave velocity with different soils characteristics